Design of a radio telemetry solar radiation sensor using solar cell - Sharif, Md. Raihan; Muhida, Riza; Ullah, M. Habib; Sulastri, Lily (EuroJournals, 2010)
Solar radiation sensor is a device that is used to measure solar radiation in W/m^2. Determining the solar radiation and its interaction with the atmosphere and the earth's surface is important because atmospheric circulation is driven by solar radiation. Moreover, solar radiation accounts for almost all of the energy available to the earth. They are also used in meteorology to measure solar radiation. Meteorology is the scientific study of the atmosphere that focuses on weather processes and forecasting. In this paper, the solar radiation sensor uses silicon solar cell or photovoltaic as sensor. Furthermore, wireless measurement system using FM transmitter and FM radio receiver is also applied. There are seven steps to obtain the final graph of the solar radiation. Firstly, a solar radiation sensor using solar cell needs to be designed. Than a photocurrent circuit is designed. The short circuit current of the solar cell is directly proportional to the energy incident on the solar cell or the solar radiation. The solar cell is used as input and the photocurrent circuit converts the current to voltage. Then signal conditioning needs to be designed so that it can amplify the voltage from the photocurrent circuit which produces a voltage in a more easily usable range. Next, a voltage-to-frequency converter is assembled that can convert measured variable information voltage from the signal conditioning into a variable frequency. Afterward, an FM Transmitter circuit is constructed that can transmit frequency to an FM radio. The output of the FM radio is analyzed and simulated using LabVIEW. Finally, after sampling and some calculation, the graph of the solar radiation is obtained.